مساهمة نظام التكاليف على أساس النشاط ABCونظام التكاليف على أساس المواصفات ABCIIفي تعظيم قيمة المؤسسة - خلايفة ريحانة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تهدف هذه الدراسة إلى إظهار كيفية مساهمة نظام التكاليف على أساس النشاط ABC ونظام التكاليف على أساس المواصفات ABCII في تعظيم قيمة المؤسسة، لذلك اخترنا مؤسسة ENICAB لصناعة الكوابل الكهربائية المتواجدة في بسكرة محلا للدراسة، بداية بدراسة واقع نظام التكاليف المطبق داخل هذه المؤسسة ومدى إمكانية قدرته على قياس التكاليف التي تساهم في قدرة الإدارة على اتخاذ القرارات اللازمة مرورا إلى تطبيق نظام ABC ونظام ABCII وإظهار دور مساهمتهم في تعظيم قيمة هذه المؤسسة. وتوصلت دراستنا إلى مجموعة من النتائج النظرية والتطبيقية أهمها: أن مهما حققت المؤسسة من نتائج مربحة من النظام القائم لديها أن الأنظمة الحديثة لإدارة التكلفة الإستراتيجية تحقق نتائج أفضل بكثير من النتائج المحققة خاصة في حال تطبيق نظام ABC ونظام ABCII، أظهرت نتائج تطبيق نظام ABC على فارق موجب في قياس تكلفة الإنتاج من الكوابل المختارة للدراسة مقارنة مع نظام التكاليف المطبق لدى المؤسسة، كما أظهرت نتائج تطبيق نظام ABCII فارق في قياس تكلفة المواصفات التي يتكون منها المنتج خلال فترة الإنجاز ويعود هذا الاختلاف إلى دقة هذه الأنظمة في التركيز على توجيه وقياس وتحديد المسار الصحيح والأنسب لتكلفة الإنتاج. وبناء على ذلك تقترح الطالبة عدة توصيات أهمها: ضرورة الاهتمام بنشر فكرة تطبيق نظام التكاليف على أساس النشاط والمواصفات لدى موظفي مؤسسة ENICABلصناعة الكوابل الكهربائية خاصة لدى موظفي قسم المحاسبة من أجل مساعدتهم على فهم الرؤية المستقبلية لإستراتيجية للمؤسسة نضرا لضرورة استخدام هذه الأنظمة التي تساهم بشكل كبير في التخطيط واتخاذ القرارات الملائمة التي تدعم فكرة التحسين الدائم والمستمر للمؤسسة. Abstract: This study aims to show how the ABC activity-based costing system and the ABCII-based costing system contribute to maximizing the value of the institution, so we chose ENICAB for the manufacture of electrical cables located in Biskra as a place of study, starting with studying the reality of the cost system applied within this institution and the extent to which it can measure costs that contribute to the ability of management to make the necessary decisions through the application of the ABC system and the ABCII system and show the role of their contribution in maximizing the value of this institution In order to achieve the objective for which this study was carried out, the student chose the ENICAB institution of electrical cable manufacturing - Biskra - as a sample for the study in order to study the reality of the cost system applied within of this institution and the measurement of its capacity to measure the costs which contribute to the capacity of the management to make the necessary decisions, passing by to the implementation of the ABC system and the ABCII system and to demonstrate the role of their contribution in the maximizing the value of this institution. Our study reached a set of theoretical and applied results, the most important of which are: No matter how profitable the results the organization achieves from using its existing system, modern systems for strategic cost management achieve much better results than the results achieved, especially if the ABC system and the ABCII system are applied., and the results of applying the ABC system showed a positive difference in measuring the production cost of the cables selected for the study compared to the cost system applied by the institution. The results of applying the ABCII system also showed a difference in measuring the cost of the specifications that make up the product during the completion period. The student thus proposes several recommendations, the most important of which are: The need to ensure dissemination of the idea of applying a cost calculation system based on activity and specifications among the employees of the ENICAB Company for the manufacture of electrical cables, especially among employees of the accounting department, in order to help them understand the future vision of the organization's strategy, considering the need to use these systems, which greatly contribute to planning and making appropriate decisions that support the idea of permanence and continuous improvement of the institution..
دراسة تطبيقية في مؤسسة ENICAB لصناعة الكوابل الكهربائية - بسكرة-
أطروحة دكتوراه تخصص محاسبة ومالية في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: نظام التكاليف على أساس النشاط، نظام التكاليف على أساس المواصفات، الأنشطة، التكاليف، تعظيم القيمة، مؤسسة ENICAB..; activity-based costing system; specification-based costing system; activities; costs; value maximization; ENICAB institutions.